Development of Motion Graphic Animation Media to Improve Rhythmic Gymnastics Skills - Audia, Lisya Widi; Sutaryono, Sutaryono (Universitas Negeri Semarang, 2021)
This study aims to develop and test the feasibility and effectiveness of motion graphic animation media in improving the rhythmic gymnastics movement skills of fourth-grade students at SDN 2 Ngabean. This research was conducted at the fourth grade of SDN 2 Ngabean.The type of this study is research and development. The results of this study indicate that motion graphic animation media is totally feasible using with the percentages of presentation worthiness by the media expert of 92.5% and the very feasible category based on material expert of 89.06%. The T test result is Tcount = 9.21138 Ttable = 1.98972, this result proved that the development of motion graphic animation media is effective to use on the learning of Physical Education for the rhythmic gymnastics skill. It is reinforced by the pre-test and post-test N-gain data of 0.406 with medium criteria. This study concludes that the motion graphic animation media are feasible and effective to use on the learning of Physical Education on the fourth-grade rhythmic gymnastics material.Keywords: Exercise Skills, Motion Graphic Animation Media, Rhythmic Gymnastics.